Antisocial-criminal Behaviors and family satisfaction in groups of high school students of fifth grade from Lima belonging to different socioeconomic levels - Ponce Díaz, Carlos (2003)
The present investigation is of corelational type and had by purpose of studying if existia relation between the conducts antisocial and the familiar satisfaction in the students of fifth of secondary one of Lima Metropolitan, pertaining to different economicos layers partner. The sample was selected traves of a no probabilistico sampling of deliberate type and was conformed by 1491 students of both sexes, that attended fifth year de secondary in 20 Educative Centers of Lima Metropolitan, of which the 7,8% (116) were of high class; the 33,5% (500), corresponded to students of middle-class; and the 58,7% (875), were level students average economico partner. The used instruments were: The Questionnaire ACCEPTS (Antisociales-Delictivas Conducts), of Nicolas Seisdedos Cubero; and Scale ESFA (SatisfactionFamiliar by Objectives), of J. Barraca and L. Lopez- Yarto, which was adapted in the present reporting the made psicometricos analisis indicated that both instruments presented/displayed trustworthiness, evaluated through metodo of internal consistency. Also, the exploratory factorial analisis and the conducted analisis of multidimensional escalamiento demonstrated that the tests are been worth.